A COMPLIANCE STRATEGY OF NATIONAL STANDARDS FOR EDUCATION IN STATE VOCATIONAL HIGH SCHOOL (SMKN 2 KISARAN) - Yahfizham Yahfizham; Wildasari Wildasari (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2020)
The results of this research are: 1) The fulfillment of national standards of education in SMK Negeri 2 of Asahan Regency as a whole is well-fulfilled, it is evidenced by the achievement of a very good accreditation level (A) of 7 (seven) programs Expertise managed by SMK Negeri 2 range; 2) The strategy of the school principal in the effort to meet the national education standards in SMK Negeri 2 The range is a delegation of authority to the subordinate based on its principal considerations, implementing supervision, monitoring, evaluation and optimizing School-owned resources; and 3) Factors that also affect the fulfillment of SNP in SMK Negeri 2 range is a commitment and solidarity, loyalty with leadership, engagement in decision making.